Development and Validation of an Augmented Reality-Based Learning Module to Enhance Historical Understanding in Secondary Education - Supardi Salam; Rizal Arizaldy Ramly; Suhenrik P; Marwan Marwan; Irwan Irwan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
he rapid development of digital technology has encouraged the integration of innovative learning media to improve the quality of education. One emerging technology with significant potential in education is Augmented Reality (AR), which provides interactive, immersive learning experiences. This study aimed to develop and evaluate an Augmented Reality-based learning module for history education using the 4-D (Define, Design, Develop, Disseminate) development model. The research employed a research and development (R&D) approach involving expert validation, limited trials, and effectiveness testing with students. Data were collected through validation sheets, questionnaires, and learning outcome tests. The results showed that the developed AR-based learning module met the criteria of validity, practicality, and effectiveness. Expert validation indicated that the module had a high level of content accuracy, instructional design quality, and media feasibility. The practicality test results demonstrated that both teachers and students responded positively to the module's usability and accessibility in classroom learning. Furthermore, the effectiveness test revealed a significant improvement in students’ learning outcomes, as indicated by higher post-test scores than pre-test scores. Therefore, the AR-based learning module can be considered an innovative and effective instructional medium to support student-centered learning and enhance learning outcomes in history education. Future research is recommended to examine the long-term impact of AR integration across different subjects and educational contexts.